2000
DOI: 10.1128/iai.68.12.6970-6978.2000
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role for the Legionella pneumophila Rep Helicase Homologue in Intracellular Infection of Mammalian Cells

Abstract: We have previously isolated 32 mutants of Legionella pneumophila that are defective in the infection of mammalian cells but not protozoa. The mutated loci have been designated macrophage-specific infectivity (mil) loci. In this study we characterized the mil mutant GK11. This mutant was incapable of growth within U937 macrophage-like cells and WI-26 alveolar epithelial cells. This defect in intracellular replication correlated with a defect in cytopathogenicity to these cells. Sequence analysis of the GK11 loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 67 publications
0
9
0
2
Order By: Relevance
“…Our data favor the prediction that it is more likely that L. pneumophila is exposed to a significantly lesser degree of stress stimuli within protozoa than within macrophages. We have recently shown that the Rep helicase of L. pneumophila, which is required for DNA repair following damage by stress stimuli, is also indispensable with mammalian cells but not within protozoa (30). These observations provide compelling evidence that although the intracellular infection is similar at the molecular and ultrastructural levels (3, 13, 26, 41), significant differences exist between the phagosomal microenvironments within protozoan and mammalian host cells.…”
Section: Discussionmentioning
confidence: 70%
“…Our data favor the prediction that it is more likely that L. pneumophila is exposed to a significantly lesser degree of stress stimuli within protozoa than within macrophages. We have recently shown that the Rep helicase of L. pneumophila, which is required for DNA repair following damage by stress stimuli, is also indispensable with mammalian cells but not within protozoa (30). These observations provide compelling evidence that although the intracellular infection is similar at the molecular and ultrastructural levels (3, 13, 26, 41), significant differences exist between the phagosomal microenvironments within protozoan and mammalian host cells.…”
Section: Discussionmentioning
confidence: 70%
“…This suggests adaptation of the rcp mutants to their environment, possibly involving the induction of other CAMP resistance mechanisms. Interestingly, a typical cytopathic effect was not elicited by the mutant; i.e., the extent of cytopathicity did not closely correlate with numbers of recovered CFU (3,32,42,50). Recently, mutants have been characterized which are defective for cytopathicity but have no intracellular growth defect and thus remain trapped inside the macrophage (1).…”
Section: Discussionmentioning
confidence: 99%
“…These communities have been identified as a causative source of infection in susceptible hosts who inhale aerosols of contaminated water containing L. pneumophila . In the human lung environment, L. pneumophila replicates exponentially within alveolar macrophages prior to lysing the host cell and invading other macrophages causing a type of walking pneumonia called Legionnaire's disease or Legionellosis (Horwitz and Silverstein, 1980; Harb and Abu Kwaik, 2000). Legionellosis has two clinically distinct forms: Legionnaires' disease, a severe type of infection, which includes pneumonia and Pontiac fever, a milder self-limiting illness (Lau and Ashbolt, 2009).…”
Section: Introductionmentioning
confidence: 99%